OUTSOURCING EMOTIONAL REGULATION: THE USE OF SMARTPHONES AND THE WEAKENING OF HUMAN MEDIATION - Alves, Werlen dos Santos; Mayer, Emerson José; Cabidel, Carla Lima de Moraes; Vargas, Tatiana de Castro Nogueira; Botechia, Carla Andréa Manenti; Valente, Marcia Andréia dos Reis Tosta; Veloso, Sinara Linhares; Ferreira, Larissa Mansk (Seven Editora, 2026)
This article analyzes digital dependence in contemporary culture from the perspective of its articulation with emotional regulation processes, with an emphasis on the outsourcing of these functions to smartphones. It starts from the premise that, in the age of hyperconnectivity, these devices have been incorporated as mediators of emotional experience, playing regulatory roles in the face of negative affective states. In this context, their use is configured as a coping strategy, highlighting the displacement of emotional mediation from human interactions to digital environments. The objective is to understand the impacts of this pattern on mental health, social relations, and educational processes, paying attention to the weakening of human mediation and the vulnerability of children and adolescents. Methodologically, this is an analytical bibliographic research, based on a critical review of the literature and the analysis of normative frameworks, with emphasis on the Digital Statute of Children and Adolescents (Law No. 15.211/2025). The results indicate harm to cognitive, emotional, and social development, as well as impairment of family interactions. It is concluded that digital addiction is a multifactorial phenomenon that requires the integration of psychological, sociocultural, and normative dimensions, with qualified mediation being central to a balanced relationship with digital technologies. The development of educational practices that promote the critical and conscious use of digital technologies is recommended.